ANALISIS KRIMINOLOGI TERHADAP TINDAK PENYIMPANGAN PERJUDIAN GAME LUDO KING MELALUI APLIKASI GAME PADA SMARTPHONE (STUDI KASUS WILAYAH POLSEK TAMBUSAI UTARA) - Sobri; Randi (SISI LAIN REALITA, 2019)
Technological advancements have brought changes to the whole social order, including games that normally can only be played real-time but are now accessible on smartphones and played online like ludo king games. Increasingly ludo king game has now changed the function of the entertainment arena into a gambling arena. The formation of this gambling event has been influenced by several factors such as economic factors, environmental factors, weak supervision factors, technological development factors. The existence of the learning process is also one of the factors in gambling in ludo king games, so that every one who plays it feels addicted to get money the wrong way. The research method in this case is a qualitative method with the aim of obtaining information by conducting direct observation to the research location and conducting in-depth interviews with key informants and informants.